Fabrication of Superhydrophobic Surfaces of TiO2 Coatings Modified with 1-Octadecanethiol - Xu, Chuyang; Wang, Yanfen; Li, Benxia; Nie, Rongchun (Asian Journal of Chemistry, 2012)
Nanoscaled rough surface modified by low-surface-energy materials has been widely used for preparation of superhydrophobic materials. In the present work, a superhydrophobic TiO2 micro/ nanostructured coating modified with 1-octadecanethiol was fabricated by a facile dip-coating process. As hydrophobization treatment by 1-octadecanethiol, the TiO2 surface changed from hydrophilic (36º) to superhydrophobic (151º), which could be attributed to the synergistic effect of the improved roughness of TiO2 and the formation of self-assembled monolayer with low surface energy.